Calcium carbonate coating on Ti-6Al-4 V by carbonate diffusion in calcium source at room temperature. (2022) - Bang, L.T.; Son, N.A.; Long, B.D.; Nhung, N.T.H.
Abstract: Titanium (Ti) and its alloy have been extensively used in orthopaedic and dental implants due to its excellent biocompatibility. However, there is still a need to improve bone integration at the early stage of implants. This study was aimed to fabricate Ti-6Al-4 V alloy coated with a bioresorbable and osteoconductive calcium carbonate (CaCO3 ). The coating was prepared by carbonate diffusion in the presence of calcium ions. The coating was characterized by grazing incidence X-ray diffraction (GIXRD), scanning electron microscope (SEM), and inductively coupled plasma atomic emission spectroscopy (ICP-AES). The GIXRD confirmed the formation of calcite phase on the surface of the Ti-6Al-4 V. The scanning electron microscope (SEM) showed that the products exhibited rhombohedral, spherical, and flower-like morphologies. The flower-like particles were orderly constructed from smaller plate-like particles with an average diameter of 5 μm. The calcium content of the coating was approximate 5.05 mg/mm 2 as detected by the ICP-AES.